1997
DOI: 10.1084/jem.185.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Apoptosis by Nitric Oxide via Inhibition of Interleukin-1β–converting Enzyme (ICE)-like and Cysteine Protease Protein (CPP)-32–like Proteases

Abstract: Physiological levels of shear stress alter the genetic programm of cultured endothelial cells and are associated with reduced cellular turnover rates and formation of atherosclerotic lesions in vivo. To test the hypothesis that shear stress (15 dynes/cm2) interferes with programmed cell death, apoptosis was induced in human umbilical venous cells (HUVEC) by tumor necrosis factor-α (TNF-α). Apoptosis was quantified by ELISA specific for histone-associated DNA-fragments and confirmed by demonstrating the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
511
5
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 788 publications
(547 citation statements)
references
References 29 publications
27
511
5
4
Order By: Relevance
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…16,27 It has been shown that NO can S-nitrosylate the catalytic cysteine of most or all caspases. [12][13][14][15][16] S-Nitrosylation inhibits protease activity of caspases and consequently prevents apoptotic death in many cell types. All caspases are expressed in cells as catalytically inactive zymogens and encounter proteolytic activation to form active enzymes during apoptosis.…”
Section: S-nitrosylation As a Potential Negative Regulator Of Excitotmentioning
confidence: 99%
See 1 more Smart Citation
“…NO, released in response to shear stress, inhibits caspase-3 activation and prevents endothelial cell apoptosis (Dimmeler et al, 1997b).…”
Section: Survival Pathwaysmentioning
confidence: 99%
“…NO can inhibit apoptosis in many cell types, including cerebellar granule neurons (Ciani et al, 2002b), human B lymphocytes (Mannick et al, 1994), ovarian follicles (Chun et al, 1995), splenocytes (Genaro et al, 1995), eosinophils (Beauvais et al, 1995), and endothelial cells (Dimmeler et al, 1997). Furthermore, NO affects apoptosis-related proteins.…”
Section: The Nnos Gene Is a Downstream Target Of The Camp Pathway Andmentioning
confidence: 99%